Surgical aspects of intestinal tuberculosis in children: Our experience - Bilal Mirza; Lubna Ijaz; Muhammad Saleem; Afzal Sheikh (Wolters Kluwer Medknow Publications, 2011)
Background: Tuberculosis (TB) is a major health problem in resource-constrained countries. Intestinal TB is especially notorious as a number of cases have to be dealt surgically, which too have morbidity and mortality. This study was conducted to identify various presentations of intestinal TB necessitating surgical intervention, their management, complications, and outcome in our hospital. Materials and Methods: This was a retrospective study carried out at the Department of Paediatric Surgery, The Children's Hospital and The Institute of Child Health Lahore, Pakistan, from December 2007 to January 2010. The information about the demography, clinical presentations, investigations, management performed, complications encountered, and outcome of patients with intestinal TB were reviewed. Results: There were a total of 18 patients with intestinal TB who were managed surgically during this period. Five were male and 13 female patients (M : F 1 : 2.6). Mean age of presentation was 8.3 years. Clinical presentations were acute peritonitis in 7 patients, pneumoperitoneum in 5 patients, complete intestinal obstruction in 4 patients, pain in right iliac fossa in 2 patients, and irreducible inguinal hernia in 1 patient. Four patients had concurrent pulmonary TB. Surgical interventions included primary repair of perforation in one, repair of perforation with diversion ileostomy in 8, and merely peritoneal drainage (haemodynamically unstable patients) in 3 patients. The post-operative complications were high output ileostomy in 3, faecal fistula in 1, wound dehiscence in 3, wound infection 5, and prolonged ileus in 1 patient. In three patients stoma was reversed during the same admission. There was one expiry in our study. Conclusion: Acute peritonitis, intestinal obstruction and intestinal perforation are the main clinical presentations requiring surgical interventions. Optimal surgical strategy should be adopted to avoid such pitfalls in the management.